Evaluating the spoken dialogue system of a conversational character: A Simulation Study - Alvarado, Yoselie (2016)
Currently, there are many applications like human-computer interactions in which speech technology plays an important role. In particular, embodied conversational character interfaces research has produced widely divergent results and it has tended to focus on the character’s dialog capabilities associated with reasoning. Conversely, the present work attempts to evaluate a conversational character from interactionrelated aspects. This paper describes an analysis of a conversational character spoken dialogue system using a discrete event simulator. The simulation model was implemented in the ARENA traditional simulator. Simulation results show that sometimes the response time from the speech conversational character can be too long to user, as well as environment noise is an important aspect of the system to be improved.